2021
DOI: 10.1007/s10980-021-01225-7
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing areas for conservation outside the existing protected area network in Bhutan: the use of multi-species, multi-scale habitat suitability models

Abstract: Context Understanding the environmental and anthropogenic factors influencing habitat selection of multiple species is a foundation for quantifying human impacts on biodiversity and developing effective conservation measures. Objectives To determine the effect of multiple scales of environmental/topographic and anthropogenic variables and landscape patterns on habitat suitability of terrestrial mammals in Bhutan, assess the effectiveness of the current pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 79 publications
3
20
0
Order By: Relevance
“…Scales used in species‐distribution modeling affected the elephant response (reflected by presence) to environmental variables and measurement of variables at coarse scales (8 km, 16 km) are more likely to reveal their links with elephant habitat selection, especially in the case of anthropogenic variables. Scale is important when exploring elephant environment relationships and its optimization is required, which has been emphasized in a case study of African savanna elephants (De Knegt et al 2011), though only 2 recent studies of Asian elephants (de la Torre et al 2021, Penjor et al 2021) account for scale optimization. The 8‐ and 16‐km radii cover areas of approximately 200 km 2 and 804 km 2 , respectively, equivalent to home‐range sizes commonly recorded for Asian elephants (Fernando et al 2008, Moßbrucker et al 2016), and are likely to account the coarse scales at which elephant presence was influenced by environmental variables.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scales used in species‐distribution modeling affected the elephant response (reflected by presence) to environmental variables and measurement of variables at coarse scales (8 km, 16 km) are more likely to reveal their links with elephant habitat selection, especially in the case of anthropogenic variables. Scale is important when exploring elephant environment relationships and its optimization is required, which has been emphasized in a case study of African savanna elephants (De Knegt et al 2011), though only 2 recent studies of Asian elephants (de la Torre et al 2021, Penjor et al 2021) account for scale optimization. The 8‐ and 16‐km radii cover areas of approximately 200 km 2 and 804 km 2 , respectively, equivalent to home‐range sizes commonly recorded for Asian elephants (Fernando et al 2008, Moßbrucker et al 2016), and are likely to account the coarse scales at which elephant presence was influenced by environmental variables.…”
Section: Discussionmentioning
confidence: 99%
“…The same effects of roads and buildings at a coarse scale have been reported for a variety of large mammals. For example, road density and buildings had the largest influence on presence of snow leopard at scales of between 19 km and 29 km in Gansu Province and Tibet (Atzeni et al 2020), and affected presence at even larger scales of 32 km for the common leopard ( Panthera pardus ), clouded leopard, and Himalaya serow ( Capricornis thar ) in Bhutan (Penjor et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cushman et al, 2010). However, Carroll et al (2001), Roberge & Angelstam (2004), Cushman & Landguth (2012) and Penjor et al (2021) demonstrated that conservation strategies based on combinations of multiple umbrella species cover broader ranges of habitat gradients, and can effectively ensure the protection of a higher fraction of sympatric species. Our analysis confirms the importance of carnivores as proxies of biodiversity and, in particular, of the more common and less specialized ones, such as Sunda stink-badger Mydaus javanensis in Borneo and Sunda leopard cat Prionailurus javanensis in Sumatra.…”
Section: Indicator Speciesmentioning
confidence: 99%
“…As the integration of three-dimensional surfaces alongside standard twodimensional predictors becomes more common in spatial modeling [28,29], the value of HSMs and HSM-derived cost surfaces for connectivity analysis will likely increase. Although realistic HSMs can help bridge the gap between connectivity modeling and conservation planning, applications of this multi-step approach have been applied only to terrestrial landscapes [26,30,31].…”
Section: Introductionmentioning
confidence: 99%